3D computational fluid dynamic modelling for pulsatile blood wave propagation in the event of car crash. Issue 4 (4th July 2017) - Feng, Jiling; An, Meiwen; Sashikumar, Sravanthi; Chen, Weiyi
ABSTRACT: Blunt traumatic aortic rupture (BTAR) is one of the leading causes of rapid fatality in motor vehicle crashes. The mechanism of BTAR, however, is still not clear due to its complicated process. This paper looks the pattern alteration of blood wave propagation of the aorta caused by impact loading to identify the sources of rupture of aorta. In this paper, a three-dimensional computational fluid dynamic (CFD) human aortic model was established. Pulsatile pressure and velocity, representing the cardiac transient pressure and velocity for the healthy adult, were applied at the inlet and outlets of aortic model as the boundary conditions. Blood flow propagation along the ascending aorta to thoracic descending aorta were analysed using ABAQUS CFD. The results indicate that the waves as a result of the impact loading have a significant effect on the patterns of blood wave propagation, which may be considered as one of the sources of rupture of aorta.